Enhancing physicochemical and leaching properties of grass jelly formulation by incorporation of gelatine - Hassan, M.F.H.; Fadhlina, A.; Nor, M.M.; Sheikh, H.I.; Yusof, Y.A.; Azman, N.A. (Rynnye Lyan Resources, 2024)
Grass jelly is a popular black jelly used in preparing various drinks and desserts. Nonetheless, preservatives and additional colourants are often used by food industries to maintain the properties of grass jelly and minimize discolouration as well as its leaching occurrence. These additives are linked with deleterious health effects and loss of vitamins in foods. The use of gelling agents such as gelatine in making grass jelly could improve its physiochemical and leaching properties. This study was designed to enhance the physicochemical (pH, colours, Brix) and textural properties of grass jelly using bovine gelatine. A texture profile analysis was conducted to analyse the hardness, springiness, gumminess and chewiness of the grass jelly. This study was also conducted to study the effect of gelatine addition on the leaching and floating properties of the grass jelly. The absorbance value of the grass jelly drink was measured in 10-minute intervals to determine its leaching occurrence while the floating analysis was done by recording the floating time. Various grass jelly formulations (GJF) were designed using a D-optimal mixture design in Design Expert® software. Data from commercial grass jelly were used as a reference during the optimization process. The amount of gelatine added to the formulations was in the range of up to 50 g (~17%). The results showed that the addition of gelatine at approximately 12.5 g (~4%) was effective in maintaining most of the physiochemical properties (L, a, b, Brix) with an overall desirability function of 0.63. This formulation was selected as the optimum grass jelly formulation (OGJF). The leaching properties and floating duration were measured on the OGJF and commercial grass jelly for 90 mins and 60 mins, respectively. The results indicated that OGJF showed a significantly (p<0.05) lower leaching rate and floating time (p<0.05). Hence, further optimization is needed to increase the floating duration of gelatine-based grass jelly.